STRATEGI MITIGASI TERHADAP RISIKO PETANI MENGHADAPI ALIH FUNGSI LAHAN (Kelurahan Setianagara, Kecamatan Cibeureum, Kota Tasikmalaya, Jawa Barat) - Nita Agresia Sijabat; Trisna Insan Noor (Universitas Galuh Ciamis, 2020)
The mitigation strategy defined as a method, a technique, or a tactic to reduce and or to prevent the negative impact of the things that could happen. The availability of the rice field in Setianegara, in the district of Cibereum, Tasikmalaya City, the Province of West Java is increasingly scarce due to the land conversion and make the farmers lose their job. This land conversion creates a lot of variety of risks and brings loss to the farmers. This research objective was to identify the priority factors that affect the risk of the farmers converse the land and to analyze the mitigation strategy over the rice field farmers to restrain the land conversion. The research design was quantitative research with survey methods. The analytical tools used in this research were the descriptive and House of Risk (HOR) analysis. The result of this research indicated that the priority factors that affected the farmers to converse the land were the building projects, unlegalized laws, the inheritance problem, and lacks of water resources. The mitigation strategy of the farmers that should be used to restrain the land conversion in Setianegara, Cibereum District, Tasikmalaya City, the Province of West Java should be : (1) planning implementation of the spatial detail, (2) establishing The LP2B: (3) assisting and counselling; and (4) improving the irrigation.